2009
DOI: 10.1016/j.jmmm.2009.01.029
|View full text |Cite
|
Sign up to set email alerts
|

A new unconventional antiferromagnet,

Abstract: We report the synthesis and basic properties of single crystals of a new binary compound, Yb3Pt4. The Yb ions in this compound are fully trivalent, and heat capacity measurements show that the crystal field scheme involves a doublet ground state, well separated from the excited states, which are fully occupied above ∼ 150 K. The heat capacity displays a large, weakly first order anomaly at 2.4 K, where a cusp is observed in the magnetic susceptibility signalling the onset of antiferromagnetic order. The entrop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 27 publications
7
19
0
Order By: Relevance
“…3 and are summarized in Table I. In accordance with detailed work on single crystals 7 , we found that variations of the site occupancies were insignificant, and therefore we fixed the sites to be fully occupied. The refined coordinates for the Yb-18f and the Pt-18f are very similar to the room temperature values found by Palenzona and, in more detail, by Bennett et al 7,13 .…”
Section: B High-resolution Neutron Powder Diffractionsupporting
confidence: 63%
See 3 more Smart Citations
“…3 and are summarized in Table I. In accordance with detailed work on single crystals 7 , we found that variations of the site occupancies were insignificant, and therefore we fixed the sites to be fully occupied. The refined coordinates for the Yb-18f and the Pt-18f are very similar to the room temperature values found by Palenzona and, in more detail, by Bennett et al 7,13 .…”
Section: B High-resolution Neutron Powder Diffractionsupporting
confidence: 63%
“…These results indicate a magnetic ordering temperature of about 2.4 K, in excellent agreement with our previous results from specific heat, dc and ac magnetic susceptibility, and electrical resistivity. 6,7 . As was also the case in these earlier measurements, we observed neither thermal hysteresis nor a sudden change in this order parameter near T N , suggesting that the ordering transition is continuous and well-described by a mean-field expression.…”
Section: B High-resolution Neutron Powder Diffractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Single crystals of Yb 3 Pt 4 were grown from lead flux 20,21 , yielding rod-like crystals with approximate dimensions of 1 × 1 × 5 mm. Powder X-ray diffraction measurements were used to verify that the crystals form in the reported rhombohedral Pu 3 Pd 4 structure type 24 .…”
Section: Methodsmentioning
confidence: 99%